The use of different by-products in the production of lightweight alkali activated building materials. (15th March 2017) - Dembovska, Laura; Bajare, Diana; Ducman, Vilma; Korat, Lidija; Bumanis, Girts
Highlights: Industrial by-products as precursor of lightweight alkali activated materials. Highly porous lightweight building materials were obtained with a density from 380 to 470 kg/m 3 . Steel plant waste retards pore formation providing homogeneous pore distribution; Alkali activation of raw materials shift the crystalline phase to an amorphous; 3D porous structure with X-ray micro-tomography was investigated; Abstract: This paper investigates the value of different industrial by-products and residues in the production of lightweight alkali activated materials (AAM). Waste metakaolin, recycled waste glass, aluminium scrap recycling waste, and steel-plant waste (SPW) were considered as secondary raw materials. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), and X-ray micro-tomography examinations were performed in order to analyse the reaction products, to identify their phase composition, and to observe the micro-morphology. The results showed that highly porous lightweight building materials could be obtained, with densities ranging from 380 to 470 kg/m 3, heat conductivities ranging between 0.14 and 0.15 W/m·K, and compressive strengths ranging between 1.1 and 2.0 MPa. It was also shown that the main hydration products were amorphous aluminosilicate gels, whereas the crystalline compounds from the SPW remained in the structure of the AAM. The results of X-ray micro-tomography showed that lightweight AAM contained 72.0–89.0 vol% of pores, with sizes ranging between 1 and 5 mm. In the paper a brief description is given of the waste management method which can be applied to obtain materials that can be used in the building industry as lightweight load-bearing insulation materials.